Comparative phenotypic and functional analysis of migratory dendritic cell subsets from human oral mucosa and skin - Kosten, Ilona Jennifer; van de Ven, Rieneke; Thon, Maria; Gibbs, Susan; de Gruijl, Tanja D. (PloS one, 2017)
Antigen exposure to oral mucosa is generally thought to lead to immune tolerance induction. However, very little is known about the subset composition and function of dendritic cells (DC) migrating from human oral mucosa. Here we show that migratory DC from healthy human gingival explants consist of the same phenotypic subsets in the same frequency distribution as DC migrating from human skin. The gingival CD1a+ Langerhans cell and interstitial DC subsets lacked CXCR4 expression in contrast to their cutaneous counterparts, pointing to different migration mechanisms, consistent with previous observations in constructed skin and gingival equivalents. Remarkably, without any exogenous conditioning, gingival explants released higher levels of inflammatory cytokines than human skin explants, resulting in higher DC migration rates and a superior ability of migrated DC to prime allogeneic T cells and to induce type-1 effector T cell differentiation. From these observations we conclude that rather than an intrinsic ability to induce T cell tolerance, DC migrating from oral mucosa may have a propensity to induce effector T cell immunity and maintain a high state of alert against possible pathogenic intruders in the steady state. These findings may have implications for oral immunization strategies.